Macrophage Fate Mapping. Issue 6 (10th June 2022) - Xu, Yingzheng; Schrank, Patricia R.; Williams, Jesse W.
Abstract: Tissue‐resident macrophages are present in all tissues where they perform homeostatic and immune surveillance functions. In many tissues, resident macrophages develop from embryonic progenitors, which mature into a self‐maintaining population through local proliferation. However, tissue‐resident macrophages can be supported by recruited monocyte‐derived macrophages during scenarios such as tissue growth, infection, or sterile inflammation. Circulating blood monocytes arise from hematopoietic stem cell progenitors and possess unique gene profiles that support additional functions within the tissue. Determining cell origins (ontogeny) and cellular turnover within tissues has become important to understanding monocyte and macrophage contributions to tissue homeostasis and disease. Fate mapping, or lineage tracing, is a promising approach to tracking cells based on unique gene expression driving reporter systems, often downstream of a Cre‐recombinase–mediated excision event, to express a fluorescent protein. This approach is typically deployed temporally with developmental stage, disease onset, or in association with key stages of inflammation resolution. Importantly, myeloid fate mapping can be combined with many emerging technologies, including single‐cell RNA‐sequencing and spatial imaging. The application of myeloid cell fate mapping approaches has allowed for impactful discoveries regarding myeloid ontogeny, tissue residency, and monocyte fate within disease models. This protocol outline will discuss a variety of myeloid fate mapping approaches, including constitutive and inducible labeling approaches in adult and embryo tissues. This article outlines basic approaches and models used in mice for fate mapping macrophages. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Adult Fate Mapping Basic Protocol 2 : Embryonic Fate Mapping